Evaluation of invalid vaccine doses in 31 countries of the WHO African Region. Issue 7 (11th February 2015) - Akmatov, Manas K.; Kimani-Murage, Elizabeth; Pessler, Frank; Guzman, Carlos A.; Krause, Gérard; Kreienbrock, Lothar; Mikolajczyk, Rafael T.
Highlights A systematic evaluation of invalid vaccinations has not been performed yet in countries of the WHO African Region. Invalid vaccinations are common in countries of the WHO African Region. Invalid vaccinations were partly associated with individual and with community associated factors. Community contextual factors should be considered when planning immunization services.